Guerra às drogas, política criminal e justiça juvenil: a repercussão do discurso da guerra às drogas nas decisões judiciais do ato infracional análogo ao tráfico - Sousa, Acássio Pereira de (2015)
The infringement act analogous to drug dealing in Brazil assumes higher rates on the application of the social-educative diligence of internment, although the act has no serious threat or violence against the victim. The relationship between the famous War on Drugs speech and these high rates on the application of the most severe social-educative precaution is significant. Therefore, it analyzes the historical construction of this discourse in the United States, Latin America and especially in Brazil and how it reverberates in the punitive system aggravation and, consequently, in the exceptional treatment given to drug dealers in recent decades. In this attempt, the Critical Criminology appears as theoretical support, specially concerning the clearing of the punitive system features. Then it analyzes the social representations of children and adolescents and how these representations impacted on the social control legislation of these social segments, especially the Juvenile Code of 1927, the Juvenile Code of 1979 and the Child and Adolescent Statute (Law no. 8.069 of 1990). The objective is to present historically the national treatment provided to the lawbreaker teenager, accentuating the current indictment system that arose from the Integral Protection Doctrine and the exceptionality assigned to the deprivation of freedom diligence. The research focuses on the jurisprudence of the 26 Courts of Justice of the states and the Court of Justice of the Federal District and the Territories, since1stof January of 2012 to31st of December of 2014. This analysis, which occurred over a Questionnaire, shows the reiteration of fundamentals concerning the War on Drugs discourseand the fading of the principles and legal hypothesis of the extreme internment diligence, to allow, in spite of the law and the Constitutional, the application of a rough treatment of adolescents accused of infraction similar to drug dealing in all regions of Brazil.